Women in China up against the wall - Schapira, Laurie Layton ([New Hampshire]: Chip Taylor Communications, 1989)
For centuries, China has been a country of many walls. The Great Wall of China is the most recognized wall in the world. This classic documentary serves two purposes. First, it dosuments the historic United Nations' Fourth World Conference on Women, which occured in Beijing in 1995, and second to offers an eye-opening look at the country and politics of China as a whole, using walls as a symbolic metaphor
Editor, Esther Truzman ; camera, Laurie Layton Schapira
DVD format
Keywords: Women -- China -- Social conditions; Women -- China -- History; China -- Politics and government; China -- Social life and customs